Estudo dos processos de obtenção de açúcares redutores totais (ART) a partir do bagaço de frutas - Mendes, Thais Pontes Pereira (2014)
Given the growing global interest in clean, renewable sources of energy, the lignocellulosic materials stand out as a potential alternative, since it does not compete with food production and are rich in sugars that can serve as a feedstock for ethanol production. Based on this context, this work aimed to study the pre-treatment and acid hydrolysis as the supply of total reducing sugars (TRS) from mango, passion fruit and pineapple bagasses (lignocellulosic materials). These materials, derived from the juice industry, underwent two chemical pretreatments with calcium hydroxide and alkaline hydrogen peroxide. The study was conducted using a 23 factorial design, using the variables of chemical reagent concentration, reaction time and temperature in order to find the best conditions that maximized the amount of available fermentable sugars. In the next stage acid hydrolysis of the study was also performed based on a 22 factorial design, using the concentration ratio and bagasse / volume of acid (solid: liquid - S: L) variables. It was found that the two studied pretreatments, mango bagasse was biomass provided more reducing sugars. Conditions which maximized the response were 24 h, 20 ° C and 1% w / v to pretreatment with alkaline hydrogen peroxide and 20 h, 40 ° C, and 0.01 g / mL for pretreatment with hydroxide calcium. These values were lower than those studied in planning in both pre-treatments. TSR was obtained 0.312 g / g of biomass pretreatment with calcium hydroxide and TSR 0.313 g / g of biomass pre-treatment with alkaline hydrogen peroxide. In the study of the hydrolysis, the pre-treatment with alkaline hydrogen peroxide proved to be more advantageous as it is used lowest acid concentration (0.5%) and higher ratio S: L (1g: 10 mL) producing higher concentrations TSR .